An Improved Adaptive Weighted Mean Filtering Approach for Metallographic Image Processing - Shao Chonglei (Journal of Intelligent Systems, 2021)
As noise brings great error in the analysis of metallographic images, an adaptive weighted mean filtering method proposed to overcome the shortcomings of the standard mean filtering method.